A comprehensive review on polymer composites in railway applications. Issue 3 (5th January 2022) - Jagadeesh, Praveenkumara; Puttegowda, Madhu; Oladijo, Oluseyi Philip; Lai, Chin Wei; Gorbatyuk, Sergey; Matykiewicz, Danuta; Rangappa, Sanjay Mavinkere; Siengchin, Suchart
Abstract: The main challenging things in railway vehicles are to reduce the consumption of energy for transportation and to decrease the emission of harmful gasses by limiting the consumption of fuel sources. These drawbacks can be overcome by lightweight structures designed for the vehicle bodies and frameworks. The composite materials with fiber reinforcements are the preferred choice for manufacturing lightweight structures to reduce the overall weight of the rail vehicle. The fiber reinforced polymer (FRP) materials possess light‐weightiness, high strength, high stiffness value and are more durable in nature. The researchers are continuously putting their efforts into new innovations in concern towards the replacement of existing conventional materials by FRP composites in railway applications. This review focuses on the overview of FRP composites, the role of composites in past rail vehicles, the rail vehicle component selection and methodology and FRP composites used for various railway components manufacturing with their challenges. Also, this review included the data of FRP composites used in various countries for different railway components applications. Hence, this review is beneficial for the upcoming researchers as a foundation literature to work on railway vehicle applications using variety of FRP materials. Moreover, the challenges are quoted in this review through the comprehensive analysis of literature and hence it provides the information in the form of research gap, so that it would be helpful for the researchers to overcome all the challenges in their upcoming research works.